Primiparae perception on guidance in prenatal care regarding breastfeeding - Monaliza Morais Teixeira; Viviane Mamede Vasconcelos; Denise Maia Alves da Silva; Elis Mayre da Costa Silveira Martins; Mariana Cavalcante Martins; Mirna Albuquerque Frota (Universidade Federal do Ceará, 2013)
The objective was to analyze the perceptions of primiparae on the guidance received in prenatal care regarding breastfeeding. Qualitative descriptive study, whose data collection happened, the period March-May 2010, through semi-structured interviews with 10 primiparae admitted to the rooming unit of a hospital in Fortaleza-CE, Brazil. For data analysis we used the content analysis, emerging the following categories: Guidelines on pre-natal care; Importance of breastfeeding; and Breast care and problems. We identified that prenatal consultation is a way to monitor the mother during pregnancy, as well as being a time to educate them about the several changes and consequences that occur during pregnancy. We concluded that mothers have a satisfactory awareness of the importance of prenatal care; however we observed a superficial knowledge apprehended in prenatal care regarding breastfeeding.